2006
DOI: 10.1093/humrep/del225
|View full text |Cite
|
Sign up to set email alerts
|

Leukaemia inhibitory factor and interleukin 11 levels in uterine flushings of infertile patients with endometriosis

Abstract: There is no receptivity defect with regard to LIF and IL-11 secretions by eutopic endometrium in infertile women with endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 25 publications
5
47
0
4
Order By: Relevance
“…These results give evidence of the transcriptional dysfunction of the NFKB during the late secretory phase in the eutopic endometrium from women with endometriosis, similar to that observed in recurrent abortion cases in which deregulation of IL6, IL1B, IL11 and LIF, cytokines related to or dependent on this system, were observed (Von Wolff et al 2000, Dimitriadis et al 2006, Mikolajczyk et al 2006. IL6 participates in endometrial function by acting as a mediator in the maternal-embryo peri-implantational communication, endometrial immune-tolerance and on inflammatory events in the implantation site (Sengupta et al 2003).…”
Section: Discussionsupporting
confidence: 75%
“…These results give evidence of the transcriptional dysfunction of the NFKB during the late secretory phase in the eutopic endometrium from women with endometriosis, similar to that observed in recurrent abortion cases in which deregulation of IL6, IL1B, IL11 and LIF, cytokines related to or dependent on this system, were observed (Von Wolff et al 2000, Dimitriadis et al 2006, Mikolajczyk et al 2006. IL6 participates in endometrial function by acting as a mediator in the maternal-embryo peri-implantational communication, endometrial immune-tolerance and on inflammatory events in the implantation site (Sengupta et al 2003).…”
Section: Discussionsupporting
confidence: 75%
“…Embryos remained unattached or became degenerated in the uterine cavity of pregnant ewes, whose uteri lacked endometrial epithelial glands and their secretions (Gray et al 2002). In humans also, infertility in some cases was found to be associated with altered levels of proteins such as leukemia inhibitory factor, proprotein convertase, and mucin-1 in the UF (Aplin et al 1996, Mikolajczyk et al 2006, Heng et al 2011. Thus, investigations of the UF in the receptive phase assume significance as these may lead to the identification of the biomarkers of endometrial function.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has become apparent now that uterine glands and their secretions continue playing an active role in terms of nutrition till the first trimester of pregnancy in humans (Burton et al 2002). Levels of leukemia inhibitory factor, mucin-1, glycodelin, vascular endothelial growth factor, and proprotein convertase 5/6 in the UF were found to be suboptimal in women with infertility (Mackenna et al 1993, Aplin et al 1996, Mikolajczyk et al 2006, Heng et al 2011. These studies showed the utility of UF analysis in gauging endometrial function.…”
Section: Introductionmentioning
confidence: 97%
“…Depleted LIF secretion and/or mutations of the LIF gene are believed to be involved in infertility in humans [15][16][17][18]. However, women with no impairment of LIF also show infertility [19,20].In the murine uterus, peak LIF expression is observed primarily in the GE and LE at estrus and at D4 [21,22]. LIF binds the LIF receptor, a heterodimer of LIF receptor β (LIFRβ) and gp130, and signals are transmitted via the Jak-Stat3 pathway [23].…”
mentioning
confidence: 99%
“…Depleted LIF secretion and/or mutations of the LIF gene are believed to be involved in infertility in humans [15][16][17][18]. However, women with no impairment of LIF also show infertility [19,20].…”
mentioning
confidence: 99%